Psychiatric Hospitalizations of People Found Not Criminally Responsible on Account of Mental Disorder in France: A Ten-Year Retrospective Study (2011–2020) - Fovet, Thomas; Baillet, Maëlle; Horn, Mathilde; Chan-Chee, Christine; Cottencin, Olivier; Thomas, Pierre; Vaiva, Guillaume; D'Hondt, Fabien; Amad, Ali; Lamer, Antoine (Frontiers in Psychiatry, 2022)
Background: Criminal responsibility is a key concept in the criminal sanctioning of people diagnosed with mental health disorders who have committed crimes. In France, based on the recommendations of one or more expert psychiatrists, a judge can declare a person not criminally responsible on account of mental disorder (NCRMD) if, at the time of the offence, the person was presenting a psychiatric disorder that abolished or altered his/her capacity for discernment and/or ability to control his/her actions. In such a case, the judge also generally orders an involuntary psychiatric hospitalization. The objectives of this study were to (1) describe longitudinal retrospective administrative data of psychiatric hospitalizations for people found NCRMD, (2) identify the age, sex, and principal diagnoses of these individuals, and (3) characterize the trajectories of their psychiatric care before and after NCRMD psychiatric hospitalization. Methods: We used discharge reports from the French national hospital database called Programme de médicalisation des systèmes d'information (PMSI) to gather longitudinal data that describe psychiatric hospitalizations for people found NCRMD between 2011 and 2020, the age, sex, and principal diagnoses of these patients, the length of their hospitalization, and the trajectories of their psychiatric care before and after their NCRMD psychiatric hospitalization. Results: We identified 3020 patients who were hospitalized for psychiatric care after having been found NCRMD between 2011 and 2020. The number of people hospitalized on these grounds has remained stable over this period, ranging from 263 in 2011 to 227 in 2021. They were mostly young men diagnosed with a psychotic disorder (62%). The majority (87%) were hospitalized in general psychiatric hospitals, and only 13% were admitted to maximum-security units (Unités pour malades difficiles, UMD). The median duration of hospitalization for these patients was 13 months. Our results show that 73% of the patients had already been hospitalized prior to their NRCMD hospitalization. The rehospitalization rate within 5 years of discharge from NCRMD psychiatric hospitalization was 62%. Conclusion: We conducted the first study investigating the psychiatric hospital treatment of people declared NCRMD in France. There is an urgent need for further studies to investigate the clinical characteristics of these patients.